The Effectiveness of Honey Consumption on Increasing Hemoglobin Levels in Young Women: A Systematic Review - Bella Christa; Hanifa Intan Khairunnisa; Saryono Saryono (International Journal of Biomedical Nursing Review, 2023)
ABSTRACT Background: Adolescents are one of the groups with a high risk of developing anemia. One of the causes of anemia is a lack of hemoglobin in the blood, so iron intake is vital for the body to make hemoglobin. Previous studies have shown that honey consumption has a positive impact on increasing hemoglobin levels. However, more research is required to determine whether honey eating can raise hemoglobin levels in female adolescents. Objective: This systematic review's objective is to determine the effectiveness of honey as a herbal ingredient for increasing hemoglobin levels in female adolescents. Methods: This study used a systematic review which was processed using the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) technique. The articles included in this study were from electronic databases that published between 2013 and 2023 in Google Scholar, Science Direct, and PubMed. The articles then extracted with due regard to the title and abstract to see their suitability for the topics discussed. Results: Out of the six papers chosen, it determined that honey increased hemoglobin levels in female adolescents. Honey contains very good nutrients to increase hemoglobin levels such as iron. The iron content contained in honey is needed to increase erythropoietin as a stimulus for erythrocyte production so that hemoglobin levels can increase. Conclusion: Consuming honey can increase hemoglobin levels in female adolescents because it contains a lot of iron, thereby minimizing the occurrence of anemia.